2014
DOI: 10.1371/journal.pone.0093400
|View full text |Cite
|
Sign up to set email alerts
|

The BRCA1 Variant p.Ser36Tyr Abrogates BRCA1 Protein Function and Potentially Confers a Moderate Risk of Breast Cancer

Abstract: The identification of variants of unknown clinical significance (VUS) in the BRCA1 gene complicates genetic counselling and causes additional anxiety to carriers. In silico approaches currently used for VUS pathogenicity assessment are predictive and often produce conflicting data. Furthermore, functional assays are either domain or function specific, thus they do not examine the entire spectrum of BRCA1 functions and interpretation of individual assay results can be misleading. PolyPhen algorithm predicted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The BRCA1 p.Ser36Tyr variant was identified in five female and a male BC patient from four unrelated families. Our group recently concluded that this BRCA1 variant demonstrates abrogated function and based on epidemiological, genetic and clinical data it is probably associated with a moderate BC risk (11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BRCA1 p.Ser36Tyr variant was identified in five female and a male BC patient from four unrelated families. Our group recently concluded that this BRCA1 variant demonstrates abrogated function and based on epidemiological, genetic and clinical data it is probably associated with a moderate BC risk (11).…”
Section: Resultsmentioning
confidence: 99%
“…In our patient cohort 33 VUS have been detected, with the majority of them being in the BRCA2 gene. In an attempt to categorize these variants, four different in silico assessment tools were applied . There was great degree of inconsistency between these predictions and hence it is impossible to draw definite conclusions on their pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that the rare variant had a relative risk of above 2 and above 4 might confer moderate and high risk of breast cancer, respectively [ 26 , 27 ]. Our study suggests that one BRCA1 variant may be associated with increased risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several of the previously published studies perform assays to study only one of the multiple functional characteristics of the BRCA1 protein separately, such as ubiquitination, transcriptional activation or homologous recombination repair (HRR). However, as BRCA1 VUSs are distributed throughout the entire protein including regions outside well-established domains, examining only a single assay may be misleading [23]. Hence, to clarify how variants in the more non-conserved parts of the protein can potentially affect its functions, there is a need for several functional assays utilising the full-length protein to mimic the more native state of the BRCA1 protein.…”
Section: Introductionmentioning
confidence: 99%